Promote Healthcare Quality Through Japanese People’s Emotional Experiences and Needs - Elokla, Nermin; Kagawa, Harumi (European Publisher, 2019)
The sustainable development goals are the blueprint to achieve a better sustainable future for all by 2030. One of these goals seeks to ensure healthy lives and promote well-being for all. Improving the health of the population means providing quality healthcare services for individuals. Recently, healthcare service focuses on patient medical care, and the physical environment's role in promoting health outcomes. Physical environment design directly impacts the patient experiences. Patient’s journey in a hospital is more than moments of medical aid and treatment—it further includes the time they spend on moving between those moments. This research identified the issues which the patients face in such a transitional area where they wait for examinations. We selected the waiting area of the gastrointestinal endoscopy unit as a case study because the patients usually wait for a period of time there before their examinations. Furthermore, there is a lack of studies discussed the design of this unit. To carry out this study, Kansei sheet was used, as well as series of interviews were conducted with 4 Japanese people with different health conditions. The intention was to capture people’s emotional experiences, and determine their demands. This study revealed that the main problems of people were related to physical space attractiveness and usability